Perancangan Model Framework Manajemen Strategik Planning Sektor Pariwisata di Provinsi Kepulauan Riau - Yuwono, Wisnu (Journal of Accounting and Management Innovation, 2018)
This research aims to design a model framework strategy planning an efficient and effective for the development of tourism sector in the province of Riau Islands, given the state of the province of Riau Islands has various advantages of geographical and geopolitical turns out to date have not been optimal in the development of tourism when seen from the results of their achievements.The research method used is a qualitative study using literature study approach on the articles published by various research journals that are directly related to the condition of tourism in Riau Islands Province, as well as articles related to strategic planning for the tourism sector in different countries.The results of this study to get a model framework beginning, starting from the perception of all stakeholders in tourism (tourists, communities, investors/companies and governments) for the development of tourism of the future, which will then be combined method RBV until finally found a strategy planning efficient and effective in the development sector Riau Islands tourism concept with through practitioner, practical and praxis, and FGD.Keywords: Framework, strategic planning, RBV, FGD